2014
DOI: 10.1089/fpd.2014.1776
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility and Molecular Typing ofSalmonellaAgona Isolated from Humans and Other Sources

Abstract: Salmonella enterica serotype Agona (Salmonella Agona) has been among the top 10 serotypes that cause human diarrheal diseases in China. A total of 95 Salmonella Agona (67 from humans, and 28 from animals, food of animal origins, and environmental sources) recovered in Shanghai, China from 2005 to 2011 were subjected to antimicrobial susceptibility testing and molecular subtyping using pulsed-field gel electrophoresis (PFGE). Approximately 68.4% of the Salmonella Agona isolates were pansusceptible to 15 antimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This serovar was first reported in Ghana, isolated from cattle, and appeared as a public health challenge in the late 1960s in the United States, Europe, and Israel. Kuang et al (150) reported that S. Agona is ranked among the top 10 serovars that cause human diarrheal diseases in China. In addition, these authors reported that most isolates were susceptible to antibacterial drugs and noted that the PFGE pattern indicated an association between isolates from humans and different animal-based foods.…”
Section: Discussionmentioning
confidence: 99%
“…This serovar was first reported in Ghana, isolated from cattle, and appeared as a public health challenge in the late 1960s in the United States, Europe, and Israel. Kuang et al (150) reported that S. Agona is ranked among the top 10 serovars that cause human diarrheal diseases in China. In addition, these authors reported that most isolates were susceptible to antibacterial drugs and noted that the PFGE pattern indicated an association between isolates from humans and different animal-based foods.…”
Section: Discussionmentioning
confidence: 99%
“…Minnesota are MDR strains, which is in line with similar observations by others for serotypes like S . Agona (Kuang et al, 2014; Irfan et al, 2015), S . Kentucky (Le Hello et al, 2013; Seiffert et al, 2014), and S .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to overall AMR prevalence, many studies compared the phenotypes and/or genotypes of isolates from different locations or sources, to address whether food could be the source of ARB for consumers. In studies based on a limited number of ARGs, virulence genes and/or phenotypes, the authors often interpreted the data to show similarity between human clinical samples and samples from food or food animals (Abdeen et al, 2021 ; Dutil et al, 2010 ; Gormley et al, 2010 ; Kuang et al, 2014 ; Overdevest, 2011 ). By contrast, studies using higher resolution methods based on whole-genome sequencing often revealed divergence between human and foodborne isolates (Acar et al, 2017 ; Campos et al, 2019 ; Cummins et al, 2022 ; Keefer et al, 2019 ; Lee et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%